An alkyne as central noninnocent ligating unit in pincer coordination: a rigid bis(indenopyridine) (NCCN)-ligand for early transition metals - Rudin, Benjamin; Eberle, Lukas; Celebcigil, Celina; Gade, Lutz H.; Ballmann, Joachim (Organometallics, 2025)
Stille coupling of two indenopyridine derivatives with a distannylated acetylene has provided convenient access to a novel bis(indenopyridine)-substituted acetylene ligand (1) featuring a rigid backbone. Upon coordination to early transition metals such as titanium, activation of the central alkyne unit was expected to induce a significant geometric distortion. This in turn would drive the reorientation of the indenopyridine wingtip units and combined with the central acetylene bonding give rise to an overall meridional arrangement. The latter is an essential feature for achieving defined [NCCN]-type coordination. In a first study of the coordination behavior of such a ligand, a highly symmetrical titanium(IV) dichloride complex (2) has been synthesized in which the metal center is stabilized by X2-type interaction with the π-coordinated alkyne. Subsequent alkylation of [NCCN]TiCl2 (2) with various organolithium and Grignard reagents provided access to a series of bis(alkyl)titanium complexes, demonstrating the synthetic accessibility of well-defined organometallic derivatives based on this ligand platform.
Im Titelzusatz steht der Ausdruck "NCCN" in eckiger Klammer
Gesehen am 15.01.2026